Quantifying water stress in vineyards using a smartphone - Livia Paleari; Lucio Brancadoro; Chiara Rusconi; Ermes Movedi; Stefano Poni; Martino Bolognini; Davide Modina; Leonardo Cunial; Matteo Gatti; Gabriele Cola; Davide Bianchi; Roberto Confalonieri (Biosystems Engineering, 2024)

Effect of multifunctional irrigation on grape quality: a case study in Northern Italy - Bianchi Davide; Bolognini Martino; Brancadoro Lucio; Cazzaniga Sara; Ferrari Daniele; Masseroni Daniele; Modina Davide; Ortuani Bianca; Pozzoli Carola; Gandolfi Claudio (Irrigation Science, 2023)
In recent decades, worldwide wine-growing regions have been affected by increasingly more frequent effects of climate change, such as long period of droughts during the growing season, summer heat waves, and late spring frost events, thus causing concern for the grape quality and production. In this context, it is necessary to develop innovative agronomic practices to counter the various negative effects from those extreme weather events, by equipping the vineyards with effective and reliable multifunctional systems, which are also economically sustainable. Particularly, a multifunctional irrigation system can be used to reduce the risk of extreme weather events and, at the same time, to improve quality and quantity of grape production, reducing their inter-annual variability as well, by providing an optimized plant water nutrition. In a vineyard situated south of Lake Garda (Northern Italy), a multifunctional irrigation system equipped with drippers and mini-sprinklers (the latter to protect from both late spring frost and summer high-temperature event) was assessed. The results obtained for the growing season 2020–21 showed that the optimized drip irrigation reduced water consumption without affecting the grape yield, both in quantity and quality. The frost protection operated by mini-sprinklers increased the air temperature at bud’s level of about 1 °C, suggesting a positive effect on plant production. Finally, in 2020, must quality was positively affected by summer sprinkler irrigation, increasing the levels of malic acid and titratable acidity of over 0.7 g L −1 while lowered total soluble solids. Further activities in the 2022 season intend to better assess the water use efficiency of this promising multifunctional system.